Kualitas SDM Eduwisata Garam pada BUM Desa Mutiara Sgahara di Desa Bunder, Kecamatan Pademawu, Kabupaten Pamekasan - Nur Hidayat, Fery; Haryanto, Rudy (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
The main purpose in this study is to determine the quality of the human resources of Bumdes Mutiara Sgahara Eduwisata Salt in Bunder Village, Pademawu, Pamekasan. This type of research is a qualitative research with a descriptive approach. Data were collected directly by the researchers from interviews with Bumdes Employee who played a role in managing salt tourism in Bunder village. This study applies indicators of the quality of human resources, namely knowledge, skills, and abilities. From the results of the discussion it can be concluded that the role of human resources is very important in relation to the success of a planning program that has been prepared. These results are expected to be useful as material for consideration for an institution in order to produce quality human resources.